Citizen Science, K-12 science education and use of technology: A synthesis of empirical research - Tsivitanidou, Olia; Ioannou, Andri (My University, 2020)
In this review, we examined the types of CS projects found in K-12 science education facilitated by digital technologies, the learning outcomes from students' participation in these projects, and the type of digital technologies used. With the application of the study's selection criteria, 15 eligible publications were included in the review; these were indexed in three databases as well as in Google Scholar. Despite the rising popularity of CS projects, the present review revealed that there is little empirical evidence for the effects of technology-facilitated CS projects on learning outcomes when K-12 students are involved. Yet, the review demonstrates a promising research area in science education and technology-enhanced learning.
Keywords: Citizen keywords science; Science education